2020
DOI: 10.1038/s41598-020-68411-6
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired TiO2 nano-cone antireflection layer for the optical performance improvement of VO2 thermochromic smart windows

Abstract: Vanadium dioxide (VO 2) is a promising material for thermochromic glazing. However, VO 2 thermochromic smart windows suffer from several problems that prevent commercialization: low luminous transmittance (T lum) and low solar modulation ability (ΔT sol). The solution to these problems can be sought from nature where the evolution of various species has enabled them to survive. Investigations into the morphology of moths eyes has shown that their unique nanostructures provide an excellent antireflection optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 54 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…The transmittance spectra of VO 2 -TTWF under the cold and hot states are measured by a SHIMADZU UV3600 UV–vis–NIR spectrophotometer. There are two vital indices to quantify the optical performance of VO 2 -TTWF, namely, the luminous transmittance ( T lum ) and solar modulation ability ( ΔT sol ). , T lum is the amount of visible light transmitted by the VO 2 -TTWF that is useful for human vision under normal conditions; it is defined as where T (λ) is the transmittance of the VO 2 -TTWF at wavelength λ. y̅ (λ) is the photopic luminous efficiency of the human eye defined by the CIE (International Commission on Illumination) standard. The wavelength range of 380–780 nm corresponds to the limits of human vision.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmittance spectra of VO 2 -TTWF under the cold and hot states are measured by a SHIMADZU UV3600 UV–vis–NIR spectrophotometer. There are two vital indices to quantify the optical performance of VO 2 -TTWF, namely, the luminous transmittance ( T lum ) and solar modulation ability ( ΔT sol ). , T lum is the amount of visible light transmitted by the VO 2 -TTWF that is useful for human vision under normal conditions; it is defined as where T (λ) is the transmittance of the VO 2 -TTWF at wavelength λ. y̅ (λ) is the photopic luminous efficiency of the human eye defined by the CIE (International Commission on Illumination) standard. The wavelength range of 380–780 nm corresponds to the limits of human vision.…”
Section: Methodsmentioning
confidence: 99%
“…They can replace conventional windows in buildings, vehicles, aircraft, and ships to save energy. Among different thermochromic materials, vanadium dioxide (VO 2 ) is widely investigated as it can modulate the transmittance of solar radiation because of its internal reversible phase change from a metal (hot state) to an insulator (cold state) at a critical-transition temperature of 68 °C. , The phase change gives rise to an abrupt change in the NIR transmittance so that VO 2 shows high transmittance in the NIR region at the cold state and becomes opaque to NIR light at the hot state. The solar energy in the NIR region accounts for around 49%, so the NIR regulation ability of VO 2 enables the window to save a lot of energy.…”
Section: Introductionmentioning
confidence: 99%
“…20a. 187 This structure is the ideal antireflective structure, which is equivalent to a dielectric layer with a continuously varying refractive index. FDTD simulation results show that the shape and distribution of VO 2 nano-cones have a significant impact on optical properties; films with a periodicity of 130 nm and aspect ratios between 1.9 and 8.8 exhibit the solar energy transmittance of 23.1% while maintaining T vis = 70.3% (Fig.…”
Section: Smart Applications Of Element-doped Vo2mentioning
confidence: 99%
“…Several works have used SiO 2 , TiO 2 , and ZrO 2 antireflective layers [37]. A more sophisticated approach was proposed by Liu et al [50], who reported the design of nanocone antireflective layers made of TiO 2 , biomimicking moth-eye morphology and reaching a T lum of 55.4%, with ∆T sol of 11.3%. Moreover, the stability of VO 2 coatings is limited by chemical and physical deterioration issues.…”
Section: Thermochromic Materialsmentioning
confidence: 99%